The effects of chemicals in isopods: a multi-organizational evaluation - Ferreira, Nuno Gonçalo de Carvalho (2018)
The global aim of this thesis was to evaluate and assess the effects of a pesticide (dimethoate) and a metal (nickel), as model chemicals, within different organization levels, starting at the detoxification pathways (enzymatic biomarkers) and energy costs associated (energy content quantification, energy consumption and CEA) along with the physiological alterations at the individual and population level (mortality), leading to a metabolomic analysis (using liquid 1H-NMR) and finally a gene expression analysis (transcriptome and RT-qPCR analysis). To better understand potential variations in response to stressors, abiotic factors were also assessed in terrestrial isopods such as temperature, soil moisture and UV radiation. The evaluation performed using biochemical biomarkers and energy related parameters showed that increases in temperature might negatively affect the organisms by generating oxidative stress. It also showed that this species is acclimated to environments with low soil moisture, and that in high moisture scenarios there was a short gap between the optimal and adverse conditions that led to increased mortality. As for UV-R, doses nowadays present have shown to induce significant negative impact on these organisms. The long-term exposure to dimethoate showed that besides the neurotoxicity resulting from acetylcholinesterase inhibition, this stressor also caused oxidative stress. This effect was observed for both concentrations used (recommended field dose application and a below EC50 value) and that its combination with different temperatures (20ºC and 25ºC) showed different response patterns. It was also observed that dimethoate’s degradation rate in soils was higher in the presence of isopods. In a similar study performed with nickel, oxidative stress was also observed. But, in the case of this stressor exposure, organisms showed a strategy where the energetic costs necessary for detoxification (biomarkers) seemed to be compensated by positive alterations in the energy related parameters. In this work we presented for the first time a metabolomic profile of terrestrial isopods exposed to stressors (dimethoate and niquel), since until the moment only a previous study was performed on a metabolomic evaluation in nonexposed isopods. In the first part of the study we identify 24 new metabolites that had not been described previously. On the second part of the study a metabolomic profile variation of abstract non-exposed organism throughout the exposure was presented and finally the metabolomic profile of organisms exposed to dimethoate and nickel. The exposure to nickel suggested alteration in growth, moult, haemocyanin and glutathione synthesis, energy pathways and in osmoregulation. As for the exposure to dimethoate alterations in osmoregulation, energy pathways, moult and neurotransmission were also suggested. In this work it was also presented the first full body transcriptome of a terrestrial isopod from the species Porcellionides pruinosus, which will complement the scarce information available for this group of organisms. This transcriptome also served as base for a RNA-Seq and a RT-qPCR analysis. The results of the RNA-Seq analysis performed in organisms exposed to nickel showed that this stressor negatively impacted at the genetic and epigenetic levels, in the trafficking, storage and elimination of metals, generates oxidative stress, inducing neurotoxicity and also affecting reproduction. These results were confirmed through RT-qPCR. As for the impact of dimethoate on these organisms it was only accessed through RT-qPCR and showed oxidative stress, an impact in neurotransmission, in epigenetic markers, DNA repair and cell cycle impairment. This study allowed the design of an Adverse Outcome Pathway draft that can be used further on for legislative purposes.